A combined docosahexaenoic acid–thyroid hormone protocol upregulates rat liver β-Klotho expression and downstream components of FGF21 signaling as a potential novel approach to metabolic stress conditions. Issue 11 (9th October 2017) - Vargas, R.; Riquelme, B.; Fernández, J.; Videla, L. A.
Abstract : We study the mechanism of how liver preconditioning by a DHA and triiodothyronine combined protocol underlies peroxisome-proliferator activated receptor α (PPARα)-fibroblast growth factor 21 (FGF21) upregulation. Abstract : Liver preconditioning by a docosahexaenoic acid (DHA) and triiodothyronine (T3 ) combined protocol underlies peroxisome-proliferator activated receptor α (PPARα)-fibroblast growth factor 21 (FGF21) upregulation, the study of the regulatory mechanisms involved being the aim of this work. Combined DHA (daily doses of 300 mg kg −1 for 3 days)–T3 (0.05 mg kg −1 at the fourth day) administration elicited higher levels of liver DHA and serum T3, with enhanced hepatic nuclear/cytosolic PPARα ratios, upregulation of FGF21 and β-Klotho expression, and a small reduction in that of FGF receptor 1 (FGFR1), compared with the respective controls. Concomitantly, the components of the FGF21 cascade extracellular-signal-regulated kinase 1/2 (ERK1/2), FGF receptor substrate 2α (FRS2α), cFos, ribosomal S6 kinase 1 (RSK1), liver kinase B1 (LKB1), and AMP-activated protein kinase (AMPK) were activated. The upregulation of liver PPARα-FGF21-AMPK signaling by the combined DHA–T3 protocol resulted in values significantly higher than those elicited by the addition of the data obtained for DHA and T3 alone. It is concluded that combined DHA–T3 supplementation achieves synergistic effects on liver PPARα-FGF21-AMPK signaling, which may result in significant metabolic changes associated with energy expenditure that are of importance in the treatment of obesity and other metabolic disorders.